ANALYSIS OF USER SATISFACTION TESTING APPLICATION USING END USER COMPUTING SATISFACTION (EUCS) METHOD - Agung Ramadhanu; Syafri Arlis; Sofika Enggari; Nabila Frisca Oktavia (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
The Office of Cooperatives and MSMEs of West Sumatra Province is a government agency engaged in the field of cooperatives and MSMEs of West Sumatra Province. The problem experienced by the Office of Cooperatives and MSMEs of West Sumatra Province is that there is no employee evaluation of the current system, namely the user satisfaction testing application. After knowing the weaknesses of the current system, a proposal was drawn to create a new questionnaire application by applying the End User Computing Satisfaction (ECUS) method which is expected from the application to measure member satisfaction with all the quality and facilities provided to members. So that with the opinions and criticisms from members of the West Sumatra Province Cooperative and MSME Office, they can carry out tests on users of the system to be designed, these tests come from active members of the West Sumatra Province Cooperative and MSME Office